Detection of leptospirosis in a dog shelter - Boo, Ao Lin (2017)
Leptospirosis is a zoonotic bacterial disease of worldwide distribution with more than one million human cases reported annually in the world. Limited study has been conducted on canine leptospirosis in Malaysia despite they may have high risk of transmitting the disease to human. The purpose of this study was to detect the canine leptospirosis and possible serovars involved in a dog shelter in Johor, Malaysia. Blood samples were collected from 73 dogs consisted of 50 vaccinated dogs and 23 non-vaccinated dogs. Microscopic agglutination test (MAT) was used to screen the serum samples for anti-leptospiral antibodies. At the cut –off titer of 1:80, two out of 73 dogs (2.7%) were seropositive for Leptospira borgpetersenii serovar Javanica. Another two out of 73 dogs (2.7%) were seropositive for L.interrogans serovar Icterohaemorrgahiae and one out of 73 dogs (1.4%) showed antibody titers against L.interrogans sv. Australis. The overall seroprevalence was 6.8% (n=5/73) in the 73 dogs studied. All seropositive dogs are vaccinated, consisting of 80% females and 20% males. The seropositive status of these shelter dogs showed that they could be potential disease disseminator to human and other animals warrant further investigation for their potential epidemiological role in leptospirosis.